New GATE Digitizer Unit for versions post v9.3 - Kochebina, Olga; Bonifacio, Daniel A. B.; Konstantinou, Georgios; Paillet, Adrien; Pommranz, Christian M.; Razdevšek, Gašper; Sharyy, Viatcheslav; Yvon, Dominique; Jan, Sebastien (Frontiers in Physics, 2024)
The Digitizer Unit plays an important role in modeling using Geant4 Application for Tomographic Emission (GATE), a Geant4-based platform used for numerical simulations in medical imaging and radiotherapy. It simulates the response of the photodetection components using a sequence of analytical and semi-analytical models. The Digitizer Unit was written for the first version of GATE approximately 20 years ago. Since then, it has in parts grown in a code that can be hardly maintained. Some parts of the code were unused or duplicated; some of the functionalities were not working anymore. Therefore, the GATE Digitizer Unit update is required in order to incorporate the novelties of Geant4 to update its current version and add new features. In this article, the implementation of the new GATE Digitizer Unit (since version 9.3) is presented. Added functionalities, the impact of changes on users, the current status of the work, and perspectives are discussed.